Fibre types of M. pectineus of the dog (Canis familiaris) - Guazzelli Filho, J.; Pai, V. D.; de Carvalho, V. C.; Orsi, A. M.; Dias, S. M. (My University, 1985)
As revealed by the NADH-diaphorase, M. pectineus of the dog possesses at least three main kind of fibres: 45.99% of small and slow contracting-red fibres, presenting an intense reaction, specially in the subsarcolemmal region; 45.55% of large and fast contracting-white fibres, presenting a less intense reaction. The remainder 8.46% fibres possess intermediate characteristics. These findings suggest that the movements of slow and fast contraction of M. pectineus are somewhat equilibrated.